2014
DOI: 10.1016/j.lindif.2014.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The moderating influence of perceived competence in learning on mentored students' school performance

Abstract: Our aim is to examine whether mentored students' Perceived Competence in Learning (PCL) moderates school performance outcomes in school-based mentoring (SBM) programs delivered by teachers. A three-stage longitudinal study was conducted in order to compare mentored (n = 157) and non-mentored students (n = 160) enrolled in formal basic education (5th to 8th grades). Multivariate Analyses of Covariance (MANCOVA) revealed that mentoring was moderately effective in improving mentees' Portuguese grades and Grade Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(58 reference statements)
0
2
0
2
Order By: Relevance
“…The Perceived Competence Scale for Learning has four items measured on a seven‐point Likert scale (1 = strongly disagree to 7 = strongly agree ) (Williams & Deci, 1996). Cronbach's alpha coefficient for the Perceived Competence Scale for Learning was 0.78, indicating excellent reliability (Simões & Alarcão, 2014). The phrase “nursing program” was added to make the four items applicable to the nursing student population.…”
Section: Methodsmentioning
confidence: 99%
“…The Perceived Competence Scale for Learning has four items measured on a seven‐point Likert scale (1 = strongly disagree to 7 = strongly agree ) (Williams & Deci, 1996). Cronbach's alpha coefficient for the Perceived Competence Scale for Learning was 0.78, indicating excellent reliability (Simões & Alarcão, 2014). The phrase “nursing program” was added to make the four items applicable to the nursing student population.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been found that such an orientation promotes deep learning, high-quality conceptual understanding, the ability to apply knowledge to new situations, and creative mathematical problem solving (Huy, 2014;Matos et al, 2017). Student engagement has also been pursued through a non-classroom mentoring procedure that has enhanced student motivation and learning (Simões & Alarcão, 2014).…”
Section: Teacher-student Interactionmentioning
confidence: 99%
“…Oppilaiden oppimisvalmiuksien kehittämiseen on pyritty myös luokkatyöskentelyn ulkopuolisen mentorointimenettelyn kautta. Tällä menettelyllä on havaittu myönteinen vaikutus oppilaiden motivoitumiselle ja oppimiselle (Simões & Alarcão, 2014).…”
Section: Opetus-oppimisprosessi Sen Ohjaaminen Ja Vuorovaikutus Oppiunclassified